A Marine-Buoy-Mounted System for Continuous and Real-Time Measurment of Seafloor Crustal Deformation - Tadokoro, Keiichi; Kinugasa, Natsuki; Kato, Teruyuki; Terada, Yukihiro; Matsuhiro, Kenjiro (Frontiers in Earth Science, 2020)
In this paper, we describe the development of a continuous real-time system capable of measuring seafloor crustal deformation using the global satellite navigation system (GNSS)/Acoustic technique and a moored buoy. A program developed was implemented on the buoy to automatically distinguish the onset of a direct acoustic wave even if that wave had been contaminated with reflected waves and to detect the true travel-times by onboard processing rather transferring raw waveforms to the ground base station. This onboard procedure contributed to reduce the data size over a satellite communication. We conducted an operations test for a total of 106 days and found that the acoustic ranging and data transmissions were frequently interrupted by an unstable power supply, resulting in only 21% of the transmitted data being received at the ground base station. Nevertheless, we did not find any problem with continuous acoustic ranging measurement except for the above-mentioned power supply failure.